Late Mississippian limestone sedimentary environment in southern Pembrokeshire (Bullslaughter Bay, Wales): evidence of meteoric diagenesis and hypersaline features. (9th May 2021) - Battiau-Queney, Yvonne; Préat, Alain; Trentesaux, Alain; Recourt, Philippe; Bout-Roumazeilles, Viviane
Abstract: Bullslaughter Bay in southern Pembrokeshire, UK, exposes sections of Upper Mississippian limestone strata. In many places, the rock suffered an isovolumetric alteration during a period of sea-level oscillations. We used multiple approaches to study the weathered rocks, combining sedimentological, petrographic and isotopic compositions (δ 18 O and δ 13 C values). Two main microfacies are recognized: (i) packstones/grainstones, characteristic of an open marine shallow subtidal/intertidal environment, with a high degree of agitation, slightly elevated salinity and temporary subaerial exposure; and (ii) mudstones/wackestones in a lagoonal setting and intertidal or supratidal environments, with a pedogenetic influence. In both cases, a complex diagenetic story, which started early in a meteoric environment, induced a strong alteration producing loose sediments in place of the parent rock. Calcretization, at or near the sediment surface in the vadose zone, was one of the most widespread diagenetic modes. It could be associated with beachrocks. Carbon and oxygen stable isotope analyses from more or less weathered limestones support the petrographic data: they show non-marine values with δ 13 C ranges of from −2.13 ‰ to 1.75 ‰ and δ 18 O from −6.05 ‰ to −4.66 ‰. These values are systematically lower than those of the middle Carboniferous seawater. Some periods of low sea level and subaerial exposure allowed gypsum to form. Neoformation of euhedral quartz by probable replacement after sulfate, and halite pseudomorphs after gypsum in a hypersaline environment are documented for the first time in southern Pembrokeshire. The studied weathered limestones present a complex diagenetic evolution related to sea-level oscillations in a range of hot and contrasting seasonal climates.